Effect of Extracorporeal Shock Wave Therapy in Conjunction with Kinetic Chain Based Exercises on Pain, Kinesiophobia, and Functional Outcome in Chronic Subacromial Pain Syndrome Participants -A Case Series - R., Kamalakannan; P., Madhuripu; Bhavika, Gohel; Vinosh Kumar, Purushothaman; HemaShangkari, Poobalan; Priyashini, Batu Malai (INTI International University, 2024)
Background and Objectives: Chronic Subacromial Pain Syndrome (CSAPS) is a common condition characterized by persistent shoulder pain and functional limitations. Despite existing non-operative treatments, patients often experience chronic pain, fear of movement (kinesiophobia) and impact shoulder function. The primary objective of this study is to evaluate the effects of extracorporeal shock wave therapy in conjunction with kinetic chain-based exercises on pain, kinesiophobia, and shoulder functional outcomes in individuals with CSAPS. Methodology: This case series included ten participants with unilateral shoulder pain lasting at least three months. Participants received extracorporeal shock wave therapy biweekly for six weeks alongside a structured kinetic chain exercise program. Outcome measures included the Numeric Pain Rating Scale for pain, the Tampa Scale for fear of movement, and the Shoulder Pain and Disability Index for functional assessment. Pre- and post-intervention data were analyzed using paired t-tests to determine statistical significance. Results and Discussion: Statistically significant improvements (p<0.05) were observed after the intervention. The average NPRS score reduced from 7.5±0.84 to 1.90±0.99, showing a significant reduction in pain. The SPADI scores exhibited a significant improvement, decreasing from 66.79±9.48 to 51.90±8.90, indicating a reduction in both shoulder pain and disability. The TSK scores decreased from 48.10±3.03 to 37.60±4.47, indicating a decrease in kinesiophobia. Conclusion: The combination of ESWT and kinetic chain exercises resulted in significant enhancements in pain reduction, reduction in fear of movement, and improvement in shoulder function. This demonstrates the potential effectiveness of this integrated strategy in controlling CSAPS.